Dark matter annihilation in the circumgalactic medium at high redshifts. Issue 3 (20th November 2017) - Schön, S; Mack, K J; Wyithe, J S B
Abstract: Annihilating dark matter (DM) models offer promising avenues for future DM detection, in particular via modification of astrophysical signals. However, when modelling such potential signals at high redshift, the emergence of both DM and baryonic structure, as well as the complexities of the energy transfer process, needs to be taken into account. In the following paper, we present a detailed energy deposition code and use this to examine the energy transfer efficiency of annihilating DM at high redshift, including the effects on baryonic structure. We employ the pythia code to model neutralino-like DM candidates and their subsequent annihilation products for a range of masses and annihilation channels. We also compare different density profiles and mass–concentration relations for 10 5 –10 7 M⊙ haloes at redshifts 20 and 40. For these DM halo and particle models, we show radially dependent ionization and heating curves and compare the deposited energy to the haloes' gravitational binding energy. We use the 'filtered' annihilation spectra escaping the halo to calculate the heating of the circumgalactic medium and show that the mass of the minimal star-forming object is increased by a factor of 2–3 at redshift 20 and 4–5 at redshift 40 for some DM models.